N-Butanol and Aqueous Fractions of Red Maca Methanolic Extract Exerts Opposite Effects on Androgen and Oestrogens Receptors (Alpha and Beta) in Rats with Testosterone-Induced Benign Prostatic Hyperplasia - Orihuela-Diaz, P; Guajardo-Correa, E (Hindawi Limited, 2017)
Benign Prostatic Hyperplasia (BPH) affects, worldwide, 50% of 60-year-old men. The Peruvian plant red maca (Lepidium meyenii) inhibits BPH in rodents. This study aimed to determine the effects of methanolic red maca extract and its n-butanol and aqueous fractions on expression of androgen and oestrogen receptors in rats with testosterone enanthate-induced BPH. Thirty-six rats in six groups were studied. Control group received 2 mL of vehicle orally and 0.1 mL of propylene glycol intramuscularly. The second group received vehicle orally and testosterone enanthate (TE) (25 mg/0.1 mL) intramuscularly in days 1 and 7. The other four groups were BPH-induced with TE and received, during 21 days, 3.78 mg/mL of finasteride, 18.3 mg/mL methanol extract of red maca, 2 mg/mL of n-butanol fraction, or 16.3 mg/mL of aqueous fraction from red maca. Treatments with red maca extract and its n-butanol but not aqueous fraction reduced prostate weight similar to finasteride. All maca treated groups restored the expression of ERβ, but only the aqueous fraction increased androgen receptors and ERα. In conclusion, butanol fraction of red maca reduced prostate size in BPH by restoring expression of ERβ without affecting androgen receptors and ERα. This effect was not observed with aqueous fraction of methanolic extract of red maca. © 2017 Diego Fano et al.